2022
DOI: 10.1007/s12144-022-03931-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and friendship quality as mediators between trait emotional intelligence and life satisfaction in Chinese adolescents: A two-wave longitudinal study

Abstract: Using a convenience sample of adolescents (N = 1609; 63.5% female; Mage = 16.54), this study explored whether EI predicted adolescent life satisfaction and whether friendship quality and optimism mediated this relationship during the COVID-19 pandemic. The structural equation modeling revealed that EI predicted adolescent life satisfaction, friendship quality, and optimism, friendship quality partially mediated the relationship between EI and life satisfaction, and optimism partially mediated the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Despite many studies conducted examining the effects of emotional intelligence and optimism on students' learning, limited research is found in identifying the relationship between emotional intelligence and optimism especially among adolescents (Tejada-Gallardo et al, 2022). It was further revealed that adolescents' lives, optimism and friendship quality can be predicted by their emotional intelligence, reflecting the moderate positive relationship between emotional intelligence and optimism (Wang et al, 2022). Interchangeably, previous studies have suggested a reverse finding where optimistic students were also the ones with high self-esteem and emotional intelligence (Checa-Domene et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…Despite many studies conducted examining the effects of emotional intelligence and optimism on students' learning, limited research is found in identifying the relationship between emotional intelligence and optimism especially among adolescents (Tejada-Gallardo et al, 2022). It was further revealed that adolescents' lives, optimism and friendship quality can be predicted by their emotional intelligence, reflecting the moderate positive relationship between emotional intelligence and optimism (Wang et al, 2022). Interchangeably, previous studies have suggested a reverse finding where optimistic students were also the ones with high self-esteem and emotional intelligence (Checa-Domene et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…Novel study suggested that support from friends does more than that. It can help our brains see the problem in a new way or "look on the bright side" better than if we tried to deal with it alone (Geers, Reilley, & Dember, 1998;Wang et al, 2022).…”
Section: Optimistic Feelingsmentioning
confidence: 99%